Historia mínima de Uruguay - Caetano, Gerardo (Ciudad de México : El Colegio de México, 2020)
Informed and well written history of Uruguay. Weaves together threads of nearly five centuries of nation's past in synthetic narration of carefully selected processes, events and agents. Author is Uruguayan former professional soccer player and esteemed historian and political scientist.
Incluye referencias bibliográficas.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2021. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Uruguay -- History; Uruguay -- Política y gobierno; Uruguay -- Historia; Uruguay -- Politics and government; Libros electrónicos